A construção alegórica em José Saramago sob o olhar da semiótica greimasiana em A jangada de pedra, Ensaio sobre a cegueira e Ensaio sobre a lucidez - Lima, Janyele Gadelha de (2021)
The present work aims to investigate how the rhetorical figure of allegory is constructed, under the bias of Greimasian Semiotics, in three works by the Portuguese author José de Sousa Saramago: A jangada de pedra (1986), Ensaiosobre a cegueira (1995) and Ensaiosobre a lucidez (2004), since the allegorical character is a point repeatedly pointed out by the Saramaguian critical fortune as one of the most singular of its literary production. For this, our research is based on Discursive Semiotics, also called Semiotics Greimasiana, in addition to theoretically relying on Greimas (1975, 1976), its main founder, we will also turn to the important contributions of Greimasian semioticians, such as Barros (1988, 2001 ), Bertrand (2003) and Fiorin (2016). Based on these theoretical references, our methodology considers the levels of the Generative Sense Path: discursive, narrative and fundamental, so that we will follow it to investigate the manifestation of allegory at each of these three levels. Thus, we started our study at the discursive level, by mapping the thematic-figurative isotopies that the enunciator uses to simulate the enunciative scene. We move on to the narrative level, where it is possible to confront the actuarial schemes most representative of the narrations placed in collation. Finally, we observe the fundamental level, the most abstract, in which we search for the categorical elements that underlie the construction of textual meaning. This path points out that the construction of meaning in the selected works presents variations in the process of formation and organization of the rhetorical resource of allegory, but that, observed in a more abstract plane, the Saramaguian allegorical expression suggests a certain semantic invariance around his project of ideological criticism of contemporary society.